2001
DOI: 10.1080/10803548.2001.11076475
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Some Organic Solvents: Hydrocarbons and Chloroalkene

Abstract: Metabolic and toxicodynamic interactions of some organic solvents in rats repeatedly treated with medium dose levels were examined. It was shown that both n-hexane and ethylbenzene significantly inhibited tetrachloroethylene metabolism during a 2-week period. n-Hexane and tetrachloroethylene enhanced metabolism of ethylbenzene whereas ethylbenzene suppressed n-hexane metabolism only at the end of the experiment. Biochemical changes, especially the drop in the level of non-protein sulfhydryl groups in tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous toxicological studies have shown that n-hexane and its metabolites, 2,5-HD and 2-hexanone, were detected in the liver, kidney, brain, blood, and the developing fetus at time points up to 18 hours after exposure [ 2 ]. 2,5-HD is known to cause testicular dysfunction, neurotoxicity, and genotoxicity and it adversely affects liver and kidney function in animals and humans [ 3 6 ]. An uncontrolled exposure to toxic industrial solvents is capable of causing biological damage which eventually could lead to pathological conditions and organ damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous toxicological studies have shown that n-hexane and its metabolites, 2,5-HD and 2-hexanone, were detected in the liver, kidney, brain, blood, and the developing fetus at time points up to 18 hours after exposure [ 2 ]. 2,5-HD is known to cause testicular dysfunction, neurotoxicity, and genotoxicity and it adversely affects liver and kidney function in animals and humans [ 3 6 ]. An uncontrolled exposure to toxic industrial solvents is capable of causing biological damage which eventually could lead to pathological conditions and organ damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In real life people are exposed to multiple chemicals or organic solvents simultaneously rather than a single agent, because most chemicals or organic solvents are the mixtures of several different kinds. Some solvents enhance the metabolism of others, while others inhibit metabolism and thereby increase solvents levels in the blood and reduce elimination time [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The level of the compounds reacting with TBA, which include MDA, is often a designated parameter in experimental animals (Skowroń et al, 2001a; 2001b) and is used as an indicator of LPO and membrane damage.…”
Section: Discussionmentioning
confidence: 99%